A GROUPOID FRAMEWORK FOR STUDY ASYMPTOTIC BEHAVIOR OF A DISCRETE SYSTEM - Mădălina Roxana BUNECI (Fiabilitate şi Durabilitate, 2017)
The purpose of this note is to introduce four different groupoids associated to a function f:XNNX, where X is a uniform space. Thesegroupoids allow to study within a unified framework theasymptotic behavior of thediscrete systems of the form xn+1 = 0 n,n f (xn,,xn-1,…, 0 n x ) that do not necessarily satisfy the semigroup property of a process. For these systems the groupoidsare associated with the functionsf defined by f(x,n,n0) := 0 n,n f (xn-1,,xn-2,…, 0 n x ) with x= 0